Similarities and differences between IL11 and IL11RA1 knockout mice for lung fibro-inflammation, fertility and craniosynostosis - Ng, Benjamin (Sci Rep, 2021)
Loss of function (LOF) in IL11RA infers IL11 signaling as important for fertility, fibrosis, inflammation and incompletely penetrant craniosynostosis. The impact of LOF in IL11 has not been characterized. We generated IL11 knockout (Il11(−/−)) mice that are born in expected ratios and have normal hematological profiles. Lung fibroblasts from Il11(−/−) mice are resistant to pro-fibrotic stimulation with TGFβ1. Following bleomycin-induced lung injury, Il11(−/−) mice are protected from pulmonary fibrosis and exhibit lesser ERK, STAT3 and NF-kB activation, reduced Il1b, Timp1, Ccl2 and diminished IL6 expression, both at baseline and after injury: placing Il11 activity upstream of IL6 in this model. Il11(−/−) female mice are infertile. Unlike Il11ra1(−/−) mice, Il11(−/−) mice do not have craniosynostosis, have normal long bone mass and reduced body weights. These data further establish the role of IL11 signaling in lung fibrosis while suggesting that bone development abnormalities can be associated with mutation of IL11RA but not IL11, which may have implications for therapeutic targeting of IL11 signaling.